Cost effectiveness of therapeutic drug monitoring for imatinib administration in chronic myeloid leukemia. - Kibum Kim; Gwendolyn A McMillin; Philip S Bernard; Srinivas Tantravahi; Brandon S Walker; Robert L Schmidt (PLoS ONE)
Background Imatinib mesylate (IM) is a first-line treatment option for patients with chronic myeloid leukemia (CML). Patients who fail or are intolerant to IM therapy are treated with more expensive second and third-generation tyrosine kinase inhibitors. Patients show wide variation in trough concentrations in response to standard dosing. Thus, many patients receive subtherapeutic or supratherapeutic doses. Therapeutic drug monitoring (TDM) may improve dose management that, in turn, may reduce costs and improve outcomes. However, TDM also adds to the cost of patient care. The objective of this study was to determine the cost-effectiveness of TDM for generic IM therapy. Methods We developed a microsimulation model for the trough plasma concentration of IM which is related to a cytogenetic or molecular response. We compared two cohorts: one with TDM and one without TDM (NTDM). The lifetime incremental cost-effectiveness ratio (ICER) was calculated using quality-adjusted life years (QALYs) as the effectiveness measure. One-way and probabilistic sensitivity analyses were performed. Results The lifetime cost and QALY of treatment with TDM were $2,137K [95% Ci: 2,079K; 2,174K] and 12.37 [95% CI: 12.07; 12.55], respectively. The cost and QALY of NTDM were $2,132K [95% CI: 2,091K; 2,197K] and 12.23 [95% CI: 11.96; 12.50], respectively. The incremental cost and QALY for TDM relative to NTDM was $4,417 [95% CI: -52,582; 32,097]) and 0.15 [95% CI: -0.13; 0.28]. The ICER for TDM relative to NTDM was $30,450/QALY. Probabilistic sensitivity analysis showed that TDM was cost-effective relative to NTDM in 90% of the tested scenarios at a willingness-to-pay threshold of $100,000/QALY. Conclusions Although the impact of TDM is modest, the cost-effectiveness over a lifetime horizon (societal perspective, ($30,450/QALY) falls within the acceptable range (< $100k/QALY).